PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH PEROLEHAN BELAJARILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Thoyyibah, Imam; Marzuki, Marzuki; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to examine whether there is the influence of the problem-based learning model on learning acquisition and test how much influence the problem-based learning model has on the acquisition of learning social science. This study uses an experimental method with the form of Pre-Experimental Design type One Group Pretest-Posttest Design. Sampling is a non probability sampling type of convenience sampling which is all class V SDN 36 Pontianak Selatan. The technique used is measurement. The data collection tool is an objective written test. The results of the average pre-test of students were 66,161 and the results of the post-test average of students were 75,207. After t test is obtained tcount 6.421 while t table with dk = 22-1 = 21 and significant level (α) = 0.05 is 1.721, it turns out tcount ≥ ttable or 6.421 ≥ 1.721 which means there is a significant effect. From the results of the calculation of the effect size (ES), ES is obtained at 0.82 with the criteria classified as high. This means that the problem-based learning model has a high influence on learning achievement in Social Sciences in fifth grade students of 36 Pontianak Pontianak State Elementary School. Problem based learning model for learning outcomes and there is a large effect on the improvement of student learning outcomes.Keywords: Problem Based Learning Model, Learning Achievement, Science Social knowledge